2015
DOI: 10.1016/j.jgg.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Carbamoyl Phosphate Synthetase 1 Deficiency Sheds Light on the Mechanism for Switching On/Off the Urea Cycle

Abstract: Carbamoyl phosphate synthetase 1 (CPS1) deficiency (CPS1D) is an inborn error of the urea cycle having autosomal (2q34) recessive inheritance that can cause hyperammonemia and neonatal death or mental retardation. We analyzed the effects on CPS1 activity, kinetic parameters and enzyme stability of missense mutations reported in patients with CPS1 deficiency that map in the 20-kDa C-terminal domain of the enzyme. This domain turns on or off the enzyme depending on whether the essential allosteric activator of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…Just as other literatures showed that most cases of CPS1D are sporadic. [13] Brain MRI data, which were limited in other case reports, were recorded in this case. Meanwhile, a new mutation founded in this case had not previously been described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Just as other literatures showed that most cases of CPS1D are sporadic. [13] Brain MRI data, which were limited in other case reports, were recorded in this case. Meanwhile, a new mutation founded in this case had not previously been described.…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity rate is 1/50,000 to 1/300,000. [1,2] The CSP1D could be onset in different ages. The normal procedure of urea cycle is interrupted as a result of the lack of carbamoyl phosphate synthetase I (CPS1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most well-known examples in mammalian cells are carbamoylphosphate synthetase (CPS1) [45] and glutamate dehydrogenase (GDH) [46]. CPS1 controls the entry of amino groups into the urea cycle and adjusts urea production to the prevalence of glutamate and arginine in the liver [47].…”
Section: Elements Of Amino Acid Signallingmentioning
confidence: 99%
“…The newly developed baculovirus/insect cell expression system, which can produce a large amount of the recombinant CPS1 with desired mutations, provides a useful tool to evaluate the residual activity, protein yield and stability of CPS1 mutants. This tool has been successfully used to study the disease-causing roles and pathogenic mechanism of various mutations in CPS1 [36,38,5154]. …”
Section: Discussionmentioning
confidence: 99%